Pengaruh Kualitas Produk dan Inovasi Produk terhadap Loyalitas Konsumen Mi Samyang dengan Kepuasan Konsumen sebagai Variabel Mediasi - Fara Agustine, Arinta; Fikriyah, Khusnul (Indonesian Journal of Islamic Economics and Business, 2025)
This study aims to analyze the effect of Product Quality and Product Innovation on Consumer Loyalty of Samyang Noodles, with Consumer Satisfaction as a Mediating Variable among Muslim Consumers in East Java. This research employs a quantitative method, utilizing primary data obtained through an online questionnaire. The sampling technique used is Purposive Sampling, with a total of 121 respondents. Data analysis is conducted using the SmartPLS 4.0 application with the Partial Least Square (PLS) approach and Structural Equation Model (SEM). The results of this study indicate that (1) Product quality has no effect on consumer loyalty, (2) Product innovation affects consumer loyalty, (3) Product quality and product innovation influence consumer Satisfaction, and (4) Product quality and product innovation do not affect consumer loyalty through consumer Satisfaction as a mediating variable